Modeling and simulation of phased array radar system - Xue, Dongming (Nanyang Technological University, 2022)
Phased array radar has been widely used. Its actual construction cost is expensive, manufacturing cycle is long and maintenance cost is high, so I choose to use computer to simulate the phased array radar system to study. Modeling and simulation of typical phased array radar systems can be done efficiently for program demonstration and performance evaluation and is an important tool for studying its key technologies. In this paper, firstly, each module in the radar system is introduced. The physical meaning and modeling method of each model are specifically analyzed, its mathematical model is established, and its simulation analysis is carried out. Based on these established simulation models, I built the whole radar system according to the design scheme of phased array radar system and verified the single target and multi-target search of the radar system. The simulation results verified the correctness of the built system.